Utilization of Jack Fruit Seeds as A Substitute of Green Nuts in Bakpia Content - Fransiscus Borgia Oki; Hari Rachmadi; Yudi Setiaji (Gastronary, 2022)
The research entitled The Utilization of Jackfruit Seeds to Replace Green Beans in Bakpia Filling uses a quantitative approach with the experimental method. Jackfruit seeds have not been used optimally and have even been discarded by the public, even though there are many benefits contained in jackfruit seeds. Researchers used jackfruit seeds as a filling material for bakpia. This study aims to determine the differences in bakpia products with jackfruit seed filling and green bean filling in terms of aroma, taste, texture, colour, and production cost and to knowing the comparison of fat, protein, and carbohydrate content of jackfruit seed bakpia with green bean bakpia through laboratory tests. The data collection method uses the hedonic test, which is taken from the respondents' assessment and includes an evaluation of aroma, taste, texture, colour, and production cost. The researcher conducted two experiments with 30 respondents from Sanggrahan Pathuk produces bakpia and asked them to complete a questionnaire. The method of analysis to differentiate respondent ratings from each aspect is through the independent sample t-test and excel t-test two-sample assuming equal variances. The results of the independent sample t-test and excel t-test two-sample assuming equal variances can be explained that has been obtained in this experiment there are no significant differences for aspects of taste, colour, aroma, texture, the t- value is 0.39, 0,39, 0,93, 0,00 which is smaller than t-table value 2,05, and for production costs there are significant differences, the t-value is 4,48 which is bigger than t-table value 2,05. It can be concluded there is no significant difference between bakpia filled with jackfruit seed and bakpia filled with green bean, except for the aspect of production costs.